MODELING OF S-SHAPED ACCUMULATION PROCESS A- AND E-CENTERS IN ISOVALENT DOPED GERMANIUM SILICON IN STATISTICA AND MATHCAD ENVIRONMENT (Modern Problems of Metallurgy, 2019)
Silicon doped with an isovalent germanium admixture (Si or SiGe in English-language scientific and technical literature) has a number of physico-technological advantages in terms of ensuring the radiation resistance of npn and npnp structures. The use of such silicon is very promising for power electronics, since it is able to supplant currently used silicon of the traditional quality, doped with phosphorus (Si ) due to its higher thermal stability and radiation resistance, which positively affects the quality of the devices manufactured on its basis. The aim of the work is to simulate nonlinear accumulation of basic radiation defects in silicon in the STATISTICA and MathCAD environment and to evaluate the possibility of using Ge as an impurity that significantly slows down the radiation degradation of Si. Nonlinear accumulation of the main radiation defects (A- and E- centers) in silicon, subjected to irradiation by α-particles, investigated. This process was simulated in the STATISTICA and MathCAD environment. Shown, that doping of silicon with germanium makes it possible substantially slow down the radiation-induced degradation of silicon up to certain doses and use of such material for manufacturing of radiation-resistant semiconductor devices, in particular, multilayered structures of high-voltage power devices of the general industrial and transport electric drive.
Keywords: silicon alloying with germanium; nonlinear accumulation of basic radiation defects; manufacturing of radiation-resistant semiconductor devices